1988
DOI: 10.1021/bi00422a004
|View full text |Cite
|
Sign up to set email alerts
|

The engineering of binding affinity at metal ion binding sites for the stabilization of proteins: subtilisin as a test case

Abstract: A weak Ca2+ binding site in the bacterial serine protease subtilisin BPN' (EC 3.4.21.14) was chosen as a model to explore the feasibility of stabilizing a protein by increasing the binding affinity at a metal ion binding site. The existence of this weak Ca2+ binding site was first discovered through a study of the rate of thermal inactivation of wild-type subtilisin BPN' at 65 degrees C as a function of the free [Ca2+]. Increasing the [Ca2+] in the range 0.10-100 mM caused a 100-fold decrease in the rate of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
142
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(151 citation statements)
references
References 38 publications
8
142
0
1
Order By: Relevance
“…A similar effect with divalent cations (and negative charges) has been noted in other protein systems (Voordouw et al, 1976;Filimonov et al, 1978;Bashford et al, 1986;Linse et al, 1988;Pantoliano et al, 1988). The effect of phosphate above its second pK, is expected to be essentially the same as sulfate.…”
Section: Effect Of Phosphatesupporting
confidence: 59%
“…A similar effect with divalent cations (and negative charges) has been noted in other protein systems (Voordouw et al, 1976;Filimonov et al, 1978;Bashford et al, 1986;Linse et al, 1988;Pantoliano et al, 1988). The effect of phosphate above its second pK, is expected to be essentially the same as sulfate.…”
Section: Effect Of Phosphatesupporting
confidence: 59%
“…The effect of Ca2+ on the stability of the apo-HRP indicates that either the acidic conditions used to remove the haem resulted in protonation of the acidic groups that led to a loss of Ca2+ from the protein, or there is an additional Caz+-binding site in the apo-HRP molecule. Evidence for additional, but much weaker, binding sites was first obtained for subtilisin when the effect of higher concentrations of Ca2+ on the kinetic thermal stability of subtilisin was studied (Pantoliano et al, 1988). Interestingly, Phelps et al (1971) compared the titration results of native and apo-HRP and they discovered that the apo-HRP had eight exposed carboxyl groups after comparing it with the native protein.…”
Section: Stabilising Effect Of Ca2+ On the Hrpmentioning
confidence: 99%
“…This structure was subsequently refined at 1.8 A resolution with phenyl methyl sulfonyl fluoride (PMSF) inhibitor covalently bound (Bott, Ultsch, Kossiakoff, Graycar, Katz & Power, 1988), in complex with Streptomyces inhibitor at 2.6 A (Hirono, Akagawa, Mitsui & Iitaka, 1984) and at 2.1 A as a complex with the chymotrypsin inhibitor 2 from barley seed (McPhalen, Svendsen, Jonassen & James, 1985;McPhalen & James, 1988). High-resolution structures of site-directed mutants of SBPN (Pantoliano et al, 1987(Pantoliano et al, , 1988 have also been reported. The three-dimensional structures of other Bacilli subtilisins have been published: the SBCARL-eglin-C complex at 1.8/k (McPhalen, Schnebli & Jamesl 1985;McPhalen & James, 1988) and independently at a nominal resolution of 1.2 A (Bode, Papamokos, Musil, Seemfiller & Fritz, 1986;Bode, Papamokos & Musil, 1987), and native SBCARL at 2.5A (Neidhart & Petsko, 1988).…”
Section: Bacteriummentioning
confidence: 99%
“…The first ion, Cal, is tightly bound and cannot be completely removed with EDTA under non-denaturing conditions, whilst the second, Ca2, is more loosely bound and can be removed with EDTA (Voordouw et al, 1976;Pantoliano et al, 1988). The effective overall negative charge of the subtilisins given in Table 4 is changed by +4 by the binding of the two calcium ions, providing both sites are fully occupied.…”
Section: Ca 2 + Sitesmentioning
confidence: 99%
See 1 more Smart Citation